PIDANA DAN TINDAKAN TERHADAP TINDAK PIDANA NARKOTIKA YANG DILAKUKAN OLEH ANAK - Priambodo, Fredyan; Sukihana, Ida Ayu (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013, 2013)
In the world of medical narcotics is necessary for the treatment and scientific study of certain types of diseases. But increasingly widespread drug abuse, even this is not only done by adults but also by children. It is necessary for the assessment of the normative perspective of legislation relating to narcotics offenses by children. Decision handed down from the judge must consider the social circumstances of the facts of the child actors. Therefore the judge must make sure that the decision to be taken is the most appropriate and fair to the child.
Keywords: Drug, Children, Decision